Animal Protein and Growth Formula: Nutrition Foundations for Children 5 Years and Older - Sitorus, Nova Lidia; Nuraeni Salsabila, Irma (Ridwan Institute, 2024)
Animal protein plays an important role in ensuring optimal nutritional intake, supporting muscle and tissue formation, and improving immunity. In addition, growth formulas specifically designed for children in this age group provide additional nutrients that may not always be met through daily food. This study aims to analyze the benefits of animal protein and growth formula in supporting physical and cognitive development in children aged 5 years and above. This study uses a qualitative research method. The data collection technique in this study was through literature studies. The data that has been collected was then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the combination of animal protein and growth milk helps children meet their daily nutritional needs required for optimal growth. These two sources of nutrition complement each other in providing a balanced intake and preventing malnutrition. The intake of protein and essential nutrients from growth milk also plays a role in increasing children's immunity, reducing the risk of disease, and supporting their mental and emotional development. Therefore, ensuring that children get enough animal protein and growth milk is essential to building a strong foundation for health and productivity in the future.